2021
DOI: 10.3389/fcimb.2021.644448
|View full text |Cite
|
Sign up to set email alerts
|

Lactulose Improves Neurological Outcomes by Repressing Harmful Bacteria and Regulating Inflammatory Reactions in Mice After Stroke

Abstract: Background and ObjectiveGut microbiota dysbiosis following stroke affects the recovery of neurological function. Administration of prebiotics to counteract post-stroke dysbiosis may be a potential therapeutic strategy to improve neurological function. We aim to observe the effect of lactulose on neurological function outcomes, gut microbiota composition, and plasma metabolites in mice after stroke.MethodsMale C57BL/6 mice (20–25 g) were randomly divided into three groups: healthy control, photothrombotic strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…Tanhuo decoction also promoted poststroke recovery by decreasing the biosynthesis of TMA, the precursor of TMAO, and increasing the expression of trimethylamine-corrinoid protein Co-methyltransferase (mttB), which catabolizes TMA to methane (69). Additionally, Lactulose supplementation was shown to significantly improve the functional outcome of stroke, which is possibly mediated by repairing intestinal barrier injury and improving gut microbiota dysbiosis following stroke (75).…”
Section: Ischemic Strokementioning
confidence: 99%
“…Tanhuo decoction also promoted poststroke recovery by decreasing the biosynthesis of TMA, the precursor of TMAO, and increasing the expression of trimethylamine-corrinoid protein Co-methyltransferase (mttB), which catabolizes TMA to methane (69). Additionally, Lactulose supplementation was shown to significantly improve the functional outcome of stroke, which is possibly mediated by repairing intestinal barrier injury and improving gut microbiota dysbiosis following stroke (75).…”
Section: Ischemic Strokementioning
confidence: 99%
“…Interestingly, oral administration of Bifidobacterium longum has achieved similar neuroprotective effects as Panax Notoginsenoside extract ( Li et al., 2018a ), which serves as an example how we could take advantage of specific species from gut microbiota for stroke recovery. In addition, atorvastatin and lactulose have already been demostrated to repair gut barrier, reduce gut inflammation and restore gut microbiota after stroke, providing novel startegies to improve stroke outcome ( Yuan et al., 2021 ; Zhang et al., 2021 ). In the future, both basic research and clinical studies on gut microbiota will open novel avenues not only for stroke therapy, but also for other brain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies demonstrated that gut microbiota plays an important role in the pathogenesis and prognosis of ischemia stroke (10,(12)(13)(14)(15)(16)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) (Table 1). For example, many studies indicate that gut microbiota can affect risk factors related to ischemia stroke directly or indirectly, including hypertension, diabetes, hypercholesterolemia, obesity and atherosclerosis, as well as aging (35,(48)(49)(50)(51)(52).…”
Section: Role Of the "Microbiota-gut-brain" Axis In The Development O...mentioning
confidence: 99%
“…Studies have shown that supplementation of Lactobacilli after stroke can reduce neuroinflammation and improve cognitive function and depression (35,40,45). In addition, new evidence indicates that lactulose and atorvastatin may regulate the structure of gut microbiota by regulating intestinal immune function and reducing neuroinflammation after stroke (43,46).…”
Section: Role Of the "Microbiota-gut-brain" Axis In The Development O...mentioning
confidence: 99%